1968
DOI: 10.1099/0022-1317-2-3-365
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Site and Sequence of Sindbis Virus Replication

Abstract: SUMMARYThe replication of Sindbis virus was studied in primary chick embryo fibroblasts treated with actinomycin D. The cellular site of viral RNA and coat protein synthesis was found to be localized in the cytoplasmic reticulum. Two different species of RNA were identified in association with the reticulum, namely a double-stranded RNA with a sedimentation constant of 20 S and RNA with a sedimentation constant of 25 S. The single-stranded RNA molecules extracted from the 130 S virus particles had a sedimentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
21
0

Year Published

1970
1970
1978
1978

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 16 publications
6
21
0
Order By: Relevance
“…In the case of Semliki forest virus (SFV), three distinct types of RNA were demon strated during viral replication, which were 42S single-stranded, 26S ribonuclease-sensi tive and 20S double-stranded forms [2]. Similar observations have been presented with another group A member, Sindbis virus (SBV) [1]. It has been concluded that the 26S RNA appearing in group A arbo virus infection has the same base ratio as the 40S single-stranded RNA obtained from purified virion [1].…”
supporting
confidence: 56%
“…In the case of Semliki forest virus (SFV), three distinct types of RNA were demon strated during viral replication, which were 42S single-stranded, 26S ribonuclease-sensi tive and 20S double-stranded forms [2]. Similar observations have been presented with another group A member, Sindbis virus (SBV) [1]. It has been concluded that the 26S RNA appearing in group A arbo virus infection has the same base ratio as the 40S single-stranded RNA obtained from purified virion [1].…”
supporting
confidence: 56%
“…At least part of the 16 to 20 S RNA's behave as the presumptive "replicative intermediates" described in the case of several arboviruses [4][5][6][7] Treatment by ribonuclease either of the whole cellular RNA's, or of the isolated 16 to 20 S RNA's, left a single homogeneous 16 S RNA peak. The ribonuclease resistant RNA was eluted from hydroxyapatite in 0.21 M phosphate buffer.…”
Section: Discussionmentioning
confidence: 99%
“…The 26 S RNA is also single-stranded and seems to be an intracellular precursor of 42 S [3]. The polydisperse 16 to 20 S species has the characteristics of both double-stranded and single-stranded RNA and seems to be the "replicative intermediate" [4][5][6][7]. Data on the lower molecular weight 10-12 S RNA's are limited and only Poir6e [4] and StoUar et al [8] have described this form.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there is a 130-140 S structure containing 40-45 S virion RNA in cells infected with group A arboviruses [2,5,8,27] including Chikungunya virus [15]. This structure corresponds to nucleocapsid (NC) of the virion in respect to its protein subunit [6,17,27], ability to yield infective RNA [5,15], morphology [8,16], and its role as a precursor of the virion as determined in pulse-chase experiments [14,27].…”
mentioning
confidence: 99%
“…This structure corresponds to nucleocapsid (NC) of the virion in respect to its protein subunit [6,17,27], ability to yield infective RNA [5,15], morphology [8,16], and its role as a precursor of the virion as determined in pulse-chase experiments [14,27]. Besides NC, there exists a 65 S component which contained single-stranded 26 S virus-specific RNA [2,5,8,27]. These were suspected to be precursors of NC and virion RNA, respectively [4,5,10].…”
mentioning
confidence: 99%